Penatalaksanaan Holistik Dermatitis Atopik Pada An. N Usia 12 Tahun Di Puskesmas Kota Karang Melalui Pendekatan Kedokteran Keluarga - Kuntum Sureda; Refi Fandana; Sahab H. Sibuea (Medula, 2023)
Atopic dermatitis also known as eczema is the most common form of chronic dermatitis. This disease is generally synonymous with itching which is characterized by dry skin, chronic lesions, and lichenification. Atopic dermatitis is believed to be associated with other forms of IgE disorders such as allergic rhinitis, asthma, and food intolerance. This disease results in a high rate of morbidity and its prevalence has increased in recent decades. The study conducted is a case report. Data were obtained through history taking and physical examination by conducting home visits. The assessment is carried out based on a qualitative diagnosis, process, and visit. Based on the examination, the patient was a 12 year old girl with atopic dermatitis. Knowledge of patients and families about the disease is very limited. Education and intervention provided to patients and families about atopic dermatitis and risk factors that can trigger the occurrence of this disease. On internal factors in cases such as genetic factors, age factors, and ignorance of the originator. External factors are the lack of family knowledge about atopic dermatitis, its complications and the environment that has many allergens. Pharmacological and non-pharmacological interventions are carried out in the form of education in preventing the onset of atopic dermatitis symptoms in patients. In the evaluation of increasing patient compliance to avoid risk factors and family knowledge about patient care. Services with a family medicine approach in pharmacological and non-pharmacological therapy are able to solve health problems and improve the patient's quality of life.